Alcohol Dehydrogenase Activity Converts 3″-Hydroxy-geranylhydroquinone to an Aldehyde Intermediate for Shikonin and Benzoquinone Derivatives in Lithospermum erythrorhizon. (18th August 2020) - Yamamoto, Hirobumi; Tsukahara, Mika; Yamano, Yumiko; Wada, Akimori; Yazaki, Kazufumi
Abstract: Shikonin derivatives are red naphthoquinone pigments produced by several boraginaceous plants, such as Lithospermum erythrorhizon . These compounds are biosynthesized from p- hydroxybenzoic acid and geranyl diphosphate. The coupling reaction that yields m- geranyl -p- hydroxybenzoic acid has been actively characterized, but little is known about later biosynthetic reactions. Although 3″-hydroxy-geranylhydroquinone produced from geranylhydroquinone by CYP76B74 has been regarded as an intermediate of shikonin derivatives, the next intermediate has not yet been identified. This study describes a novel alcohol dehydrogenase activity in L. erythrorhizon cell cultures. This enzyme was shown to oxidize the 3″-alcoholic group of ( Z )-3″-hydroxy-geranylhydroquinone to an aldehyde moiety concomitant with the isomerization at the C2′–C3′ double bond from the Z -form to the E -form. An enzyme oxidizing this substrate was not detected in other plant cell cultures, suggesting that this enzyme is specific to L. erythrorhizon . The reaction product, ( E )-3″-oxo-geranylhydroquinone, was further converted to deoxyshikonofuran, another meroterpenoid metabolite produced in L. erythrorhizon cells. Although nonenzymatic cyclization occurred slowly, it was more efficient in the presence of crude enzymes of L. erythrorhizon cells. This activity was detected in both shikonin-producing and nonproducing cells, suggesting that the aldehyde intermediate at the biosynthetic branch point between naphthalene and benzo/hydroquinone ring formation likely constitutes a key common intermediate in the synthesis of shikonin and benzoquinone products, respectively.